Sistem Inventory Barang Gudang Berbasis Web Studi Kasus Yayasan Indonesia Care - Adzani, Adinda Mutiara; Mulya, Citra Pricylia Ananda; Ahluna, Faza; Febrianti, Syafira; Akbar, Yuma; Yel, Mesra Betty (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Along with the increasingly rapid development of technology, this can be characterized by increasingly sophisticated technology. Using computers as a tool in carrying out work in information technology is becoming increasingly common and developing in all fields. This research discusses implementing an equipment inventory information system at the Indonesia Care Foundation to increase the efficiency of managing equipment availability. This study includes requirements analysis, system design, and implementation of information technology-based solutions to monitor and manage equipment more effectively. Data collection methods involve interviews, observation, and documentation analysis. The research results show that implementing an inventory information system provides significant benefits, including increased recording accuracy, more efficient stock management, and better monitoring of equipment use and maintenance. This implementation's success positively contributes to operational efficiency and improves equipment management performance at the Foundation Indonesia Care.